2021
DOI: 10.1101/2021.05.23.21257669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploiting Molecular Basis of Age and Gender Differences in Outcomes of SARS-CoV-2 Infections

Abstract: Motivation: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (coronavirus disease, 2019; COVID-19) is associated with adverse outcomes in patients. It has been observed that lethality seems to be related to the age of patients. Moreover, it has been demonstrated that ageing causes some modifications at a molecular level. Objective: The study aims to shed out light on a possible link between the increased COVID-19 lethality and the molecular changes that occur in elderly people. Methods: W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…18 Growing evidence suggested that HMGA2 may be associated with tumorigenesis in a variety of cancers, including lung, breast, kidney and gastric cancers. 8,9,11,19 In our present study, we identified HMGA2 as a down-stream target of miR-103a, and our data revealed that miR-103a directly regulate the expression of HMGA2. These data suggested that SNHG1 promoted RCC proliferation through upregulated HMGA2 by sponging miR-103a.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…18 Growing evidence suggested that HMGA2 may be associated with tumorigenesis in a variety of cancers, including lung, breast, kidney and gastric cancers. 8,9,11,19 In our present study, we identified HMGA2 as a down-stream target of miR-103a, and our data revealed that miR-103a directly regulate the expression of HMGA2. These data suggested that SNHG1 promoted RCC proliferation through upregulated HMGA2 by sponging miR-103a.…”
Section: Discussionsupporting
confidence: 60%
“…HMGA2, a member of high mobility group AT‐hook family, is characterized as an oncofetal protein which is hardly expressed in the differentiated tissues, whereas is highly expressed in a variety of tumors 18 . Growing evidence suggested that HMGA2 may be associated with tumorigenesis in a variety of cancers, including lung, breast, kidney and gastric cancers 8 , 9 , 11 , 19 . In our present study, we identified HMGA2 as a down‐stream target of miR‐103a, and our data revealed that miR‐103a directly regulate the expression of HMGA2.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot is based on testing the effectiveness of the wearable device for monitoring the healthcare status of older adults after covid-19 vaccination [1,2].…”
Section: Ofmentioning
confidence: 99%
“…The current version of the GTEx database (v8 accessed on August 22th) stores 17382 samples of 54 tissues of 948 donors, see at https://gtexportal.org/home/tissueSummaryPage. GTEx is available through a web interface that offers easy to use query interface and visualisation of data in tissues, and it is used in many ageing-related studies [24,25,26,27]. Despite this, to our knowledge, the GTEx data portal has some limitations, such as (i) users cannot query data grouped by age or sex, and (ii) data are not integrated with existing protein interaction databases.…”
Section: Introductionmentioning
confidence: 99%